Head injury screening and intimate partner violence: A brief report. Issue 4 (8th August 2017) - Gagnon, Kerry L.; DePrince, Anne P.
ABSTRACT: Objective : Although the importance of traumatic brain injury has gained public attention in recent years, relatively little attention has been paid to head injuries among women who have experienced intimate partner violence (IPV). The present study screened for lifetime exposure to mild traumatic brain injuries (mTBIs) among a sample of women who had experienced recent IPV (median days since target incident = 26). Method : Participants included ethnically diverse women whose IPV experiences were reported to law enforcement. Women ( n  = 225) were asked about injuries to the head sustained during the target IPV incident as well as over the lifetime, and related symptoms. Results : The vast majority of women (80%) reported a lifetime head injury. More than half (56%) screened positive for mTBI, defined as at least one instance in which they experienced a change in consciousness or a period of being dazed and confused as a result of a head injury. A minority of women (13%) reported injuries to the head during the target IPV incident. Most women who had experienced a lifetime head injury reported frequent and current cognitive difficulties. Conclusion : These findings highlight the importance of assessing head injuries and related symptoms among women who have experienced IPV, pointing to important implications for policy and practice.